Correlations among antiangiogenic factors and trace elements in hypertensive disorders of pregnancy - Rezende, Vania B. (2015)
Although a number of studies have measured circulating levels of some trace elements in preeclampsia (PE) and compared to healthy pregnant (HP), there is no consensus yet about the deficiency of some metals and development of hypertensive disorders in pregnancy. The aim of this study was to compare plasmatic levels of Zn, Mn, Co, Cu, Se and Sr among non-pregnant (NP), healthy pregnant (HP), gestational hypertensive (GH) and preeclamptic (PE) women and to correlate these levels with plasma soluble endoglin (sENG) and soluble fms-like tyrosine kinase-1 (sFLT-1), two important antiangiogenic proteins related to PE. A total of 184 women were enrolled in this study (NP = 35, GH = 51, PE = 37 and HP = 61). Trace element analyses were carried out with an inductively coupled plasma mass spectrometer (ICPMS). sENG and sFLT-1 plasma concentrations were measured by commercial ELISA kits. The most interesting result is that Sr is higher in PE (63%, P<0.001) compared to HP and their levels are positively correlated with sENG in all three groups of pregnant women. Moreover, we found a negative correlation between Zn and sENG in HP (r=-0.43, P=0.003). Regarding other elements, we found similar levels among pregnant groups. In conclusion, this study showed that Sr may has a role in physiopathology of PE. (C) 2014 Elsevier GmbH. All rights reserved.